Ayurvedic preparation of Zingiber officinale Roscoe: effects on cardiac and on smooth muscle parameters. Issue 18 (17th September 2018) - Leoni, Alberto; Budriesi, Roberta; Poli, Ferruccio; Lianza, Mariacaterina; Graziadio, Alessandra; Venturini, Alice; Broccoli, Massimiliano; Micucci, Matteo
Abstract: The rhizome of the Zingiber officinale Roscoe, a biennial herb growing in South Asia, is commonly known as ginger. Ginger is used in clinical disorders, such as constipation, dyspepsia, diarrhoea, nausea and vomiting and its use is also recommended by the traditional medicine for cardiopathy, high blood pressure, palpitations and as a vasodilator to improve the circulation. The decoction of ginger rhizome is widely used in Ayurvedic medicine. In this papery by high-performance liquid chromatography, we have seen that its main phytomarkers were 6-gingerol, 8-gingerol and 6-shogaol and we report the effects of the decoction of ginger rhizome on cardiovascular parameters and on vascular and intestinal smooth muscle. In our experimental models, the decoction of ginger shows weak negative inotropic and chronotropic intrinsic activities but a significant intrinsic activity on smooth muscle with a potency on ileum is greater than on aorta: EC50  = 0.66 mg/mL versus EC50  = 1.45 mg/mL. Abstract :